Three-level converter in offshore wind energy systems: new strategy for unbalancing in capacitors voltage - Melício, Rui (2014)
This paper is on offshore wind energy conversion systems with full-power three-level converter and permanent magnet synchronous generator. The multi-level converters, namely three-level converters are limited by unbalance voltages in the direct current link capacitors. In order to lessen this limitation, a new control strategy for the selection of the output voltage vectors is proposed. The aim is to evaluate the performance of the three-level converter with the new strategy.